ЦИВІЛЬНО-ПРАВОВЕ РЕГУЛЮВАННЯ ТРАНСПЛАНТОЛОГІЇ В УКРАЇНІ ТА ІНОЗЕМНИХ ДЕРЖАВАХ - Герц, Алла Анатоліївна, Олійник Роман Володимирович (SUPREMANCE OF LAW, 2019)
The article is devoted to the transplantation of organs and biological materials to man as one of the most effective, and sometimes unconventional ways to save human life. The new Law of Ukraine ««On the application of transplantation of anatomical materials to man» will save the lives of thousands of Ukrainians. Regulation of transplantation at the level of law in Ukraine, as in other post-Soviet states, has been implemented with considerable delay, as doctors and lawyers have repeatedly pointed out. For example, the law of Denmark ««On the taking of tissues of the human body and other biological materials» was adopted in 1967, the law of Brazil ««On the taking of tissues, organs and body parts of the dead for medical and scientific purposes» - in 1968, the law of France ««On taking organs «- in 1976. Transplantation of organs and other anatomical materials is a special method of treatment, which consists in transplantation of the organ recipient or other anatomical material taken from a person or animal. The Civil Code of Ukraine uses a single term - donation - as regards blood and its components, as well as for organs and other anatomical materials. Th e fundamentals of Ukrainian health legislation, as well as special laws in this regard, establish two terms: 1) donation of blood and its components; 2) transplantation of organs and other anatomical materials. The Law of Ukraine ««On the application of transplantation of anatomical materials to a person» provides for a presumption of disagreement of the deceased on the donation of his anatomical materials. Th at is, material for transplantation can be obtained from the body of a deceased person only if he has agreed to the transplant during his lifetime. By comparison, in many countries of the European Union (Belgium, Austria, Spain, Czech Republic, Great Britain, Hungary, Sweden, Finland), as well as in Belarus, the law provides for the presumption of a persons consent to post-mortem donation. Under the law of the Republic of Belarus «On the Transplantation of Human organs and tissues», a person who does not want her organs used for transplantation may, during a lifetime, express his disagreement, which is entered into the relevant Registry. Ukraine on the way of humanization of society will fi nd opportunities to solve urgent problems in the fi eld of transplantology and reach the European level of medical care for patients.